Tame the kitten - Mori, Bianca (Mandaluyong City Anvil Publishing, Inc., 2015)
Kit Torres can't believe her awful luck when she's assigned to babysit a motorcycling superstar for her boss. But sexy sparks fly when he teaches her all about the finer aspects of control. Can Kit keep her cool when the race starts to heat up? Fab Magnani lives on the edge of disaster -- he makes a good living out of it as a pro racer. Will his instincts for squeezing out of danger serve him when he comes face to face with an Puerto Rican spitfire who takes an instant dislike to him?
Spark Books is an imprint of Anvil Publishing, Inc.
Keywords: Motorcycling -- Fiction; Erotic literature; New York -- Fiction